Peripherally restricted viral challenge elevates extracellular glutamate and enhances synaptic transmission in the hippocampus. Issue 2 (3rd June 2016) - Hunsberger, Holly C.; Wang, Desheng; Petrisko, Tiffany J.; Alhowail, Ahmad; Setti, Sharay E.; Suppiramaniam, Vishnu; Konat, Gregory W.; Reed, Miranda N.
Abstract: Peripheral infections increase the propensity and severity of seizures in susceptible populations. We have previously shown that intraperitoneal injection of a viral mimic, polyinosinic‐polycytidylic acid (PIC), elicits hypersusceptibility of mice to kainic acid (KA)‐induced seizures. This study was undertaken to determine whether this seizure hypersusceptibility entails alterations in glutamate signaling. Female C57BL/6 mice were intraperitoneally injected with PIC, and after 24 h, glutamate homeostasis in the hippocampus was monitored using the enzyme‐based microelectrode arrays. PIC challenge robustly increased the level of resting extracellular glutamate. While pre‐synaptic potassium‐evoked glutamate release was not affected, glutamate uptake was profoundly impaired and non‐vesicular glutamate release was augmented, indicating functional alterations of astrocytes. Electrophysiological examination of hippocampal slices from PIC‐challenged mice revealed a several fold increase in the basal synaptic transmission as compared to control slices. PIC challenge also increased the probability of pre‐synaptic glutamate release as seen from a reduction of paired‐pulse facilitation and synaptic plasticity as seen from an enhancement of long‐term potentiation. Altogether, our results implicate a dysregulation of astrocytic glutamate metabolism and an alteration of excitatory synaptic transmission as the underlying mechanism for the development of hippocampal hyperexcitability, and consequently seizure hypersusceptibility following peripheral PIC challenge. Peripheral infections/inflammations enhance seizure susceptibility. Here, we explored the effect of peritoneal inflammation induced by a viral mimic on glutamate homeostasis and glutamatergic neurotransmission in the mouse hippocampus. We found that peritoneal inflammation elevated extracellular glutamate concentration and enhanced the probability of pre‐synaptic glutamate release resulting in hyperexcitability of neuronal networks. These mechanisms are likely to underlie the enhanced seizure propensity. Abstract : Peripheral infections/inflammations enhance seizure susceptibility. Here, we explored the effect of peritoneal inflammation induced by a viral mimic on glutamate homeostasis and glutamatergic neurotransmission in the mouse hippocampus. We found that peritoneal inflammation elevated extracellular glutamate concentration and enhanced the probability of pre‐synaptic glutamate release resulting in hyperexcitability of neuronal networks. These mechanisms are likely to underlie the enhanced seizure propensity.